Mobbing y personalidad en profesionales de Enfermería. Riobamba, 2020 - María Cecilia, Vistín Castillo , Adriana Carolina Sánchez Acosta (2021)
The present investigation aimed to analyze mobbing and personality traits in nursing professionals in Riobamba, 2020. The project was carried out with 50 nurses, 35 women and 15 men, ranging from 25 to 50. The research was of a documentary and field type, a cross-sectional design, and a descriptive level. The instruments applied were: Questionnaire of harassment strategies at work LITP-60 and Personality Test of 16 PF, which were used to verify the presence of mobbing and personality traits. One of the most outstanding results was that 70% of professionals present mobbing within the ranges, low, moderate, and high, in addition to considering age and gender as risk factors. Regarding personality, the predominant traits were affability, stability, dominance, animation, attention to norms, daring, sensitivity, abstraction, privacy and perfectionism. Considering the presence of 60% or more in each of them, showing mostly low and high scores that correspond to characteristics of people with a personality profile with low pole extraversion is introverted and socially inhibited. He also presented hardness in high pole; this means reserved people, resistant to change. Based on the results obtained, a psychological therapeutic plan in presented, which aims to prevent and reduce mobbing.